PREDICTION OF FACIAL EXPRESSION USING DEEP LEARNING - R., PUNITHAVATHI M.E.; T. , NAVEEN KUMAR; S., D.PONGOWTHUM; A. , RAHUL; S. , SANTHOSKUMAR (International Journal of Psychosocial Rehabilitation, 2020)
Recommendation suggestion is one of the biggest problems for modern-day applications and their developers. It deals with the content delivery and advertisement, where matching the service provider and the client who requires the service are happening. Now a days, the history and the wish list of the application user are not enough to satisfy the requirements of the user. The real-time emotion of humans needs to be founded out in order to provide the right content to the right user. It can be made possible by building a convolutional neural network using deep learning, where the model will be trained with several thousand images, and then input is passed and output is returned.